Potential Use of Waste Biodrying Products as Cofiring Steam Power Plants (PLTU Labuhan Angin) - Harianja, Ria Wenny; Zaman, Badrus; Huboyo, Haryono Setiyo (International Journal Labs, 2025)
Sustainable waste management is an important challenge in facing the energy and environmental crisis. One of the solutions that has begun to be developed is the use of biodrying technology, which is the process of drying organic waste using biological activity and aeration to reduce moisture content and increase the calorific value. This study aims to examine the potential of waste biodrying products as an alternative fuel in the cofiring process at the Labuhan Angin Steam Power Plant (PLTU). The methodology used includes the analysis of biodrying product characteristics, measurement of calorific values, as well as technical and environmental feasibility studies in cofiring applications. The results show that biodrying products have a calorific value that is competitive enough to be used as a partial substitute for coal, and can reduce carbon emissions and environmental burden. The implementation of cofiring with waste biodrying has the potential to contribute to the clean energy transition and reduce the volume of waste disposed of in landfills.